Using artificial ground murals to promote restorative sidewalk experiences: Effects of colors and patterns on mood, perceived restorativeness, and heart rate in virtual reality - Gu, Lanqing; Roe, Jenny; Knöll, Martin (Journal of environmental psychology, 2025)
Ground murals have been applied in streetscapes to improve walkability, pedestrian safety, and social interaction. However, limited research explores how the design of murals enhances environmental qualities associated with restorative experiences in urban gray streetscapes. This study employed a 3 × 2 mixed design, with color (warm, cool, and achromatic) as a within-subjects factor and pattern (angular and curvilinear) as a between-subjects factor, to explore the effects of ground mural design features on subjective mood states, heart rate (HR), and perceived restorativeness (PR). Virtual reality (VR) was used to simulate a gray commercial street with high motorized traffic volumes in Darmstadt, Germany. Students (n = 83) from Darmstadt were separated into two pattern design groups and underwent a virtual walk through the scenario without murals, with each color condition in a reverse counterbalanced order. Pre- and post-mood states were assessed by mood statements, and PR was rated using an adjusted Perceived Restorativeness Scale (PRS). Changes in pre-post physiological arousal were measured using wearable sensors capturing HR change. Results revealed that color was a critical design factor for ground murals affecting restorative experiences. In an urban gray sidewalk setting, ground murals with cool and achromatic colors and curvilinear patterns significantly improved PR, while warm-colored murals increased energetic arousal and reduced relaxation. When comparing design conditions, cool colors were perceived as more relaxing than warm colors. Chromatic designs enhanced pleasure and energetic arousal compared to achromatic designs. No HR change difference was observed between conditions. This is the first study pairing street ground mural design features with physiological and psychological responses within a VR experimental context. It provides insights for cost-effective color and pattern urban design interventions that could support mental health and well-being. •A physical street setting was simulated in an immersive virtual environment.•Sidewalks with murals can enhance restorative experiences in a gray street setting.•Different color schemes elicited varied responses in mood.•No difference in mood or perceived restorativeness was observed between pattern conditions.